The understanding towards plagiarism among students at Faculty of Pharmacy Universiti Teknologi MARA Puncak Alam - Che Hamid, Nur Farihah Syuhada (2017)
Plagiarism is a serious academic issue and must be addressed properly. In this paper we report the results of a survey of student plagiarism at the Faculty of Pharmacy, UiTM Puncak Alam. This survey examined the understanding towards plagiarism among undergraduate pharmacy students and the reasons behind the plagiarism activities. By using sample size of 256 respondents this study found out that majority of students have a higher understanding towards plagiarism. This study also found that lack of understanding is not one of the factors that cause students to plagiarize. However, most students admitted that the other reason why they plagiarize is because they never attended any formal course on plagiarism. So, it is recommended that the faculty take an initiative by conducting a seminar on plagiarism in future in order to decrease the incidence of plagiarism.